The Complete Mitochondrial Genomes of Six Species of Tetranychus Provide Insights into the Phylogeny and Evolution of Spider Mites - Chen, Da-Song (Public Library of Science, 2014)
Many spider mites belonging to the genus Tetranychus are of agronomical importance. With limited morphological characters, Tetranychus mites are usually identified by a combination of morphological characteristics and molecular diagnostics. To clarify their molecular evolution and phylogeny, the mitochondrial genomes of the green and red forms of Tetranychus urticae as well as T. kanzawai, T. ludeni, T. malaysiensis, T. phaselus, T. pueraricola were sequenced and compared. The seven mitochondrial genomes are typical circular molecules of about 13,000 bp encoding and they are composed of the complete set of 37 genes that are usually found in metazoans. The order of the mitochondrial (mt) genes is the same as that in the mt genomes of Panonychus citri and P. ulmi, but very different from that in other Acari. The J-strands of the mitochondrial genomes have high (∼84%) A+T contents, negative GC-skews and positive AT-skews. The nucleotide sequence of the cox1 gene, which is commonly used as a taxon barcode and molecular marker, is more highly conserved than the nucleotide sequences of other mitochondrial genes in these seven species. Most tRNA genes in the seven genomes lose the D-arm and/or the T-arm. The functions of these tRNAs need to be evaluated. The mitochondrial genome of T. malaysiensis differs from the other six genomes in having a slightly smaller genome size, a slight difference in codon usage, and a variable loop in place of the T-arm of some tRNAs by a variable loop. A phylogenic analysis shows that T. malaysiensis first split from other Tetranychus species and that the clade of the family Tetranychoidea occupies a basal position in the Trombidiformes. The mt genomes of the green and red forms of T. urticae have limited divergence and short evolutionary distance.